"Conservación de la papaya (Carica papaya L.) con aplicación de bacterias ácido lácticas provenientes del mucilago de cacao (Theobroma cacao)". - Salazar Daza, Diana Cecilia (2020)
Reducing high fruit losses requires the adoption of several measures during harvestihandling, storage, packaging and processing of fresh fruits and vegetables to obtain suitproducts with better storage properties. Among these fruits we have papaya, which tropical fruit, with a high content of vitamin C that helps to strengthen the immune system the human being. At present, the demand for agricultural products with good sensory nutritional characteristics and free of microorganisms has increased, for this reason objective of this research was to evaluate the conservation of papaya with the application lactic acid bacteria from cocoa mucilage. A Completely Random Design (DCA) was carrout with a bifactorial AxB arrangement, study factors factor A lactic acid bacteria (0, 5, 10extracted from cocoa mucilage of trinitarian origin CCN51 and as factor B time in days 7, 14 days), obtaining 9 treatments with 3 repetitions and using the Tukey rank test at 5%the comparison of means of the treatments to be studied. The physical-chemical parameevaluated of pH, ° Brix and acidity showed significant differences, being T9 (10% BALDays) the treatment that maintained the best storage properties after the 14-day storage tiRegarding the appearance of colorimetry, it was observed that the color of the fruit remaineat adequate levels. Keywords: storage, sensory characteristics, fresh fruits, fruit processing, shelf life.